Desenvolvimento de aplicações usando composição de serviços dirigida pelo usuário - Guido, Alex Roberto (2016)
One of the Software Engineering challenges is the development of applications that can adapt to the heterogeneous needs of users. Technical Dynamic Composition of Services Driven by User is a solution for developing applications capable of overcoming these challenges. This type of application which will call User-Driven Service Composition Application (UDSCA) allows to compose services during its execution, thus meeting the needs of users. But the lack of guidance on how to develop UDCAs can make it difficult or even impossible to build these applications, because it may aggregate unknown solutions by developers. Looking supply this lack, this work presents an approach to guide developers during the development of this kind of application. To develop the approach, it has been defined which activities should be undertaken during the development as well as the concepts, techniques, artifacts, technologies and tools needed to perform these activities. To evaluate the approach one conducted a case study in which a UDSCA was developed in the field of building maintenance services. The resulting application of the approach was shown to be able to adapt to the heterogeneous needs of the user, also the approach provided artifacts that promoted reuse. In conclusion, the approach guides the developer during the UDSCAs development and provides artifacts that reduce efforts for development.